Ex-situ conservation of Climbing plants at University of Agricultural Sciences, Bangalore, Karnataka - Editor, M. H. Rajkumar and M. D. Rajanna (Recent Research in Science and Technology, 2011)
Ex-situ conservation center for climbing plants has been established at the Botanical Garden, University of Agricultural Sciences, GKVK, Bangalore. The Botanical garden of this university is of unique type adopting systematic classification for conservation plants of Karnataka in particular and country in general. The dedicated Climber plants block has the collectionÃ‚Â  More than 50 species collected from all parts of the Karnataka, which are used by various tribals and local people to cure different ailments ranging from simple injuries, wounds, cuts, fever, diarrhea, ulcers, swelling, bone fractures, potency, antidote, skin care, night blindness, toothache, asthma, cough & cold. The present study work provides detailed account of Climbing shrub and woody climber plants conserved with their unique uses.